The Implementation of Sharf Learning Using KH. Muhammad Yusuf's Method at Terbuka Junior High School Wanar Lamongan / Penerapan Pembelajaran Sharf dengan Menggunakan Metode KH Muhammad Yusuf di SMP Terbuka Wanar Lamongan - Fivi Nur Alifah; Muhammad Thohir (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2020)
A lot of sentence changes in Arabic make it difficult for students to interpret Arabic texts, students lack understanding about the meaning of words that have changed from the original form to another form. The purpose of this study is to find out in depth about the sharf learning process at The Open Junior High School by using the KH Muhammad Yusuf sharf method, and also to find out the supporting factors and inhibiting factors in this method. This study used a descriptive qualitative method with data sources, namely direct interviews with teachers at SMP located in the village of Wanar, Lamongan Regency. The results of this study are the students required to memorize a wazan along with examples in one day. The focus of the material on the four bina’ which are most often found in Arabic texts. The supporting factors in this study are sharf books, teachers, and boarding schools. While the inhibiting factors in this study are student motivation and student background at the previous level of education. Keywords: Learning Arabic, Sharf, KH Muhammad Yusuf Method Abstrak Perubahan kalimat yang banyak dalam bahasa Arab membuat siswa kesulitan dalam mengartikan teks yang berbahasa Arab, siswa kurang memahami tentang arti kata yang telah berubah dari bentuk asal ke bentuk lain. Tujuan dari penelitian ini adalah ingin mengetahui secara mendalam tentang proses pembelajaran sharf di SMP Terbuka dengan menggunakan metode sharf KH Muhammad Yusuf, dan ingin mengetahu faktor-faktor pendukung serta factor penghambat dalam metode ini. Penelitian ini menggunakan metode kualitatif desrkriptif dengan sumber data yaitu wawancara langsung terhadap guru di SMP Terbuka yang terletak di desa Wanar Kabupaten Lamongan. Hasil dari penelitian ini adalah siswa di wajibkan menghafalkan satu wazan beserta contohnya dalam waktu satu hari. Serta fokus materi pada empat bina’ yang paling sering di temukan di tek-teks berbahasa Arab. Adapun faktor pendukung dalam pembelajaran ini adalah kitab sharf, guru, dan asrama pesantren. Sedangkan faktor penghambat dalam pembelajaran ini adalah motivasi siswa serta latar belakang siswa pada jenjang sebelumnya. Kata Kunci: Pembelajaran Bahasa Arab, Sharf, Metode KH Muhammad Yusuf